POLY(4-VINYLBENZYL) TRIMETHYLAMMONIUM CHLORIDE-CO-(4-VINYLBENZYL)-N-METHYL-D-GLUCAMINE) COPOLYMER WITH REMOVAL PROPERTIES FOR VANADIUM (V) AND MOLYBDENIUM(VI). ADSORPTION ISOTHERM STUDY - D V Morales; M Torregosa; B L Rivas; M Gonzalez (Journal of the Chilean Chemical Society, 2022)
It was studied the removal properties of poly(4-vinylbenzyl) trimethylammonium chloride–co-(4-vinylbenzyl)-N-methyl-D-glucamine) P(ClVBTA-co-VBNMDG) ion exchange resin towards vanadium (V) and molybdenum (VI), and compared with commercial  resin Amberlite  IRA-743 which contains the same functional group. The resin was characterized by FT-IR spectroscopy and SEM. Parameters like water adsorption capacity, effect of the pH, maximum retention capacity of the metal ions, elution, regeneration, selectivity, interferents effect, adsorption time, and adsorption isotherms were studied. All the studies were carried out by Batch equilibrium procedure. Thermodynamic parameters such as enthalpy, entropy, and free energy were calculated. The P(ClVBTA-co-VBNMDG) resin showed higher capacity to remove V(V) and Mo(VI) from water solution than that Amberlite IRA-743 commercial resin. The higher capacity displayed by P(VBNMDG) resin was attributed to the higher degree of swelling and the stronger active functional groups.